Migrating out of mega-cities: Evidence from Brazil - Eva-Maria Egger (IZA Journal of Development and Migration, 2021)
Traditional economic models predict rural to urban migration during the structural transformation of an economy. In middle-income countries, it is less clear which direction of migration to expect. In this article, the author shows that in Brazil as many people move out as into metropolitan cities and they mostly move to mid-sized towns. The author estimates the determinants of out-migrants' destination choice accounting for differences in earnings, living costs, and amenities and tested whether the migrants gain economically by accepting lower wages but enjoying lower living costs. The findings suggest that in their destination choice, out-migrants aim to minimize costs of moving. On average, city-leavers realize higher real wages, including low-skilled migrants who would lose in nominal terms. The article thus provides new evidence on economic incentives to leave big cities in a middle-income country.
Keywords: J61; R23; C35; 330; internal migration; secondary towns; living costs; Brazil